The textile reader - Hemmings, Jessica (Bloomsbury Visual Arts, 2023)
Addressing textiles as a distinctive area of cultural practice and field of scholarly research, The Textile Reader introduces students to the key issues essential to the exploration of the textile from both a critical and a creative perspective. The second edition brings together lectures, catalogue essays, academic articles, fiction and poetry, as well as several articles available in English translation for the first time, to capture the diversity of voices informing textile studies today"